Creutzfeldt-Jakob Disease: Alterations of Gut Microbiota - Guo, Yanjun; Xu, Yichen; Lin, Xue; Zhen, Zhen; Yi, Fang; Guan, Hongzhi; Shi, Qi; Sun, Wenjie; Yang, Anchao; Dong, Xiaoping; Wang, Jiawei (Frontiers in Neurology, 2022)
Introduction: Human gut dysbiosis has been implicated with many neurodegenerative disorders. However, current data focus on the gut microbiota of CJD patients is still lacking. In our study, we explored the gut microbiota alteration in CJD patients. Method: We performed 16S ribosomal RNA Miseq sequencing in stool sample of CJD patients and controls. Functional analysis of gut microbiota between groups was based on KEGG and PICRUSt2. Clinical rating scales were used to evaluate the association of cognitive impairment with gut microbiota alteration. Result: We identified a significant alteration in both the structure and the richness in CJD group. Function analysis revealed that CJD gut microbiota was enriched in immune, signaling molecules interaction and xenobiotics biodegradation. MoCA and survial time were found to associate with gut microbiota in CJD. Conclusion: We demonstrated an altered gut microbiota in CJD patients, which were associated with the cognitive impairment and the survival time.